COVID-19 vaccine hesitancy and associated factors among infertile couples undergoing assisted reproductive treatment - Wang, Xinyan; Wang, Huiyan; Du, Aijun; Wang, Junchao; Shi, Jie; Zhang, Yunshan; Zhang, Yinfeng; Ma, Junfang; Meng, Wenjia; Lv, Jiabei; Luo, Haining (Frontiers in Immunology, 2022)
Vaccine hesitancy is an important threat to the public health in this COVID-19 pandemic era. Although the COVID-19 vaccine hesitancy in China was modest, little was known about it among infertile couples. Thus, we conducted this cross-section survey among infertile patients in a reproductive medicine center, 9/2021-12/2021 to estimate the prevalence of COVID-19 vaccine hesitancy and the coverage rate of the primary, and to explore the contributing factors. Information on socio-demographic characteristics, clinical characteristics, attitudes toward the COVID-19 pandemic and the vaccine, etc. was collected through unified questionnaire. Among the 987 included interviewees, 17.33% reported hesitancy in the primary vaccination, 25.63% reported hesitancy in the booster vaccination, and 32.32% delayed the primary vaccination. Hesitancy in the primary vaccination was associated with unexplained infertility (OR: 1.77, 95% CI: 1.05-2.98), ongoing IVF treatment (OR: 2.17, 95% CI: 1.22-3.89), concerns for vaccine safety (OR: 4.13, 95% CI: 2.66-6.42), effectiveness (OR: 1.62, 95% CI: 1.15-2.28), and influence on pregnancy (OR: 2.80, 95% CI: 1.68-4.67). These factors were also associated with hesitancy in the booster vaccination. Delay of the primary vaccination was inversely associated with a college or above degree (OR: 0.49, 95% CI: 0.27-0.87), previous history of influenza vaccination (OR: 0.67, 95% CI: 0.46-0.98), and positively associated with concerns for the influence on pregnancy (OR: 7.78, 95% CI: 5.01-12.07). The prevalence of COVID-19 vaccination hesitancy and delay of the vaccination were higher among infertile patients than the general population. Concerns for vaccine safety, effectiveness, influence on pregnancy, and ongoing ART treatment were associated with higher prevalence of vaccine hesitancy and delay of the primary vaccination.